Registration of USDA‐N7005 soybean germplasm with high yield and 62.5% pedigree from Japanese accessions Tamahikari and PI 416937. Issue 3 (6th June 2022) - Bagherzadi, Laleh; Gillen, Anne M.; McNeece, Brant T.; Mian, Rouf; Song, Qijian; Talierico, Earl; Fallen, Ben; Li, Zenglu; Carter, Thomas E.
Abstract: USDA‐N7005 soybean [ Glycine max (L.) Merr.] (Reg. no. GP‐457, PI 699962) was released by the USDA‐ARS and the North Carolina Agricultural Research Service in August 2021. USDA‐N7005 is an early‐maturity group VII, F4 ‐derived germplasm with excellent yield potential that traces 62.5% of its pedigree to Japanese accessions that are not part of the historical genetic base of U.S. soybean breeding. Currently, Japanese germplasm constitutes only a small portion of the U.S. soybean base. USDA‐N7005 was derived from the cross of cultivar 'USDA‐N7002' × Japanese cultivar 'Tamahikari'. USDA‐N7005 traces 12.5% of its ancestry to Japanese landrace PI 416937 via USDA‐N7002 and 50% to Japanese cultivar Tamahikari. USDA‐N7005 is the second public release in the United States derived from Tamahikari. Over 13 environments of the United Soybean Board Southern Diversity Yield Trials and 19 test environments of the USDA Uniform Soybean Tests‐Southern States, USDA‐N7005 yielded 108% ( p  < .05) and 101% of the adapted parent cultivar USDA‐N7002, respectively, and matured 2–3 d earlier. The new release also yielded 100% of check cultivars 'NC‐Roy' and 'USDA‐N7003CN' and 96% of cultivar 'NC‐Dilday' in the Uniform Tests. USDA‐N7005 was similar in height and lodging to parent USDA‐N7002 but exhibited elevated seed oil content and larger seed size. USDA‐N7005 was resistant to root‐knot nematode and stem canker, with resistance comparable to that of resistant parent USDA‐N7002. The superior agronomic performance and diverse pedigree of USDA‐N7005 make it desirable parental stock for broadening the base of U.S. soybean breeding. Core Ideas: USDA‐N7005 is an early MG VII conventional germplasm with excellent yield potential. USDA‐N7005 traces 62.5% of its pedigree to Japanese accessions. USDA‐N7005 is the second public release in the United States derived from Tamahikari. USDA‐N7005 is resistant to root‐knot nematode and stem canker.